Spontaneous ventricular thrombosis in patients with inflammatory bowel disease. (20th November 2017) - Pak, Stella; Linares, Juan; Yatsynovich, Yan; Cha, David; Nye, Dexter; Kaminski, Diana; Costello, Jillian
Abstract: Inflammatory bowel disease is closely associated with an increased risk for thrombotic events. Thrombosis mostly occurs in the extremities, lungs, and liver; but it can also occur in the ventricles of the heart. The primary goal of this article is to increase awareness of the risk for ventricular thrombosis in this patient population among healthcare professionals and, thus, appropriate prompt use of thromboprophylaxis therapy for these patients during acute flare-ups. Early diagnosis and intervention are critical for ventricular thrombosis to prevent systemic embolisation of the thrombus. Concisely, inflammatory bowel disease predisposes to the development of thrombi. A low threshold for the use of imaging studies to detect such thrombi is warranted.